2016
DOI: 10.1021/acs.organomet.6b00444
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among 31P NMR Coordination Chemical Shifts, Ru–P Bond Distances, and Enthalpies of Reaction in Cp′Ru(PR3)2Cl Complexes (Cp′ = η5-C5H5, η5-C5Me5; PR3 = PMe3, PPhMe2, PPh2Me, PPh3, PEt3, PnBu3)

Abstract: The 31P NMR spectra of CpRu­(PR3)2Cl and Cp*Ru­(PR3)2Cl complexes with PR3 = PMe3, PPhMe2, PPh2Me, PPh3, PEt3, P n Bu3 have been measured; these data correlate with and can be used to predict Ru–P bond distances and enthalpies. Their 31P NMR coordination chemical shifts (Δ­(ppm) = δcomplex – δfree) show significant linear correlations with literature values of both the enthalpies of the ligand exchange reactions to form the Ru–P bonds and the average Ru–P bond distances from crystal structures. The strong corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…In the 31 P NMR spectra, the signals of phosphine ligands appeared at 29.3 ppm for 2, at −2.6 ppm for 3 and at 11.9 ppm for 4. Such chemical shifts were in good agreement with the data for similar phosphine complexes of other transitional metals [24].…”
Section: Resultssupporting
confidence: 89%
“…In the 31 P NMR spectra, the signals of phosphine ligands appeared at 29.3 ppm for 2, at −2.6 ppm for 3 and at 11.9 ppm for 4. Such chemical shifts were in good agreement with the data for similar phosphine complexes of other transitional metals [24].…”
Section: Resultssupporting
confidence: 89%
“…To this end, addition of two equivalents (0.05 mmol) of triphenylphosphine to a solution of 1 in CDCl 3 (~0.75 M) resulted in a rapid color change from dark green to purple upon heating at 70 °C for one hour. The 1 H NMR spectrum of this solution revealed complete disappearance of signals attributed to Ru‐bound arene C–H's (δ = 5.81, 5.66, 5.58, and 5.29, Figure ), while the 31 P{ 1 H} NMR spectrum exhibited a new signal at δ = 17.40 consistent with the chemical shifts observed for related arene Ru(II) complexes . Combined, these data suggest loss of the p ‐cymene ligand to form a complex such as [ L1 ‐Ru(PPh 3 ) 2 Cl] BF 4 with two equivalent triphenylphosphine ligands, likely requiring a κ 3 ‐N,N,S binding mode to complete the coordination sphere.…”
Section: Resultssupporting
confidence: 62%
“…31 P NMR data were recently applied for correlation of both steric and electronic parameters of phosphine ligands in transition‐metal complexes, particularly, the Ru⋅⋅⋅P distances and coordination chemical shifts were linearly correlated . In this work we found that there is a positive correlation between the δ ( 31 P) chemical shifts for PNP−Ce III complexes 1 – 6 measured in benzene and experimentally estimated Ce III −P bond distances ( R= 0.965, Figure ).…”
Section: Resultsmentioning
confidence: 53%